Development in long-term prognosis of first-time myocardial infarction in relation to use of guideline-recommended treatments: Danish total population cohort study. (3rd October 2022) - Christensen, D M; Schjerning, A; Smedegaard, L; Charlot, M; Phelps, M; Gerds, T; Gislason, G; Sehested, T S G
Abstract: Background: Evidence from randomized trials during the previous decades have led to several improvements in acute and secondary preventive treatments for myocardial infarction (MI). However, there is a lack of recent knowledge about the implementation of these treatments and how they affected developments in the long-term prognosis of MI. Purpose: To investigate developments in long-term outcomes after first-time MI and their relation to use of guideline-recommended treatments in a contemporary total population cohort. Methods: All patients with a first-time MI from 2001 to 2018 were identified through Danish nationwide registries with follow-up through October 6, 2021. The study period was divided into 3-year periods. In each period, the Aalen-Johansen method was used to estimate the absolute 1-year risk for mortality, recurrent MI, heart failure, bleeding hospitalization, and ischemic stroke. The relative frequencies of pharmaceutical treatments and use of coronary procedures were calculated. In each calendar period, the 1-year mortality and recurrent MI risk was standardized to the 2016–2018 distribution of patient characteristics, procedure use, and treatment initiation. Treatment, standardized risks, and recurrent MI risk were evaluated in patients who survived to day 28 post discharge. Results: In total, 134, 884 patients (median age 69 years, 36.5% female) were included and 120, 473 survived to day 28 post discharge (median age 68 years, 35.2% female). From 2001–2003 to 2016–2018, the 1-year risks of mortality (23.5% to 12.1%), recurrent MI (6.8% to 3.2%), and ischemic stroke (1.8% to 1.3%) decreased. Risk of heart failure remained relatively stable, whereas the 1-year risk of bleeding hospitalization increased from 2.1% to 3.0%. This pattern remained consistent during very long durations of follow-up (Figure 1). Initiation of statins (58.0% to 86.4%) and adenosine diphosphate receptor inhibitors (42.5% to 85.6%) increased considerably. Use of coronary angiography (37.3% to 84.5%) and percutaneous coronary intervention (24.8% to 63.5%) also increased. There was an attenuated decrease in the standardized 1-year risks of mortality and recurrent MI compared to the observed reference risks: from 8.7% (reference: 11.1%) in 2001–2003 to 6.1% in 2016–2018 for mortality and from 5.6% (reference: 6.8%) in 2001–2003 to 3.1% in 2016–2018 for recurrent MI (Figure 2). Conclusions: There was a substantial improvement in the long-term risk of mortality and recurrent MI for patients with first-time MI. This improved prognosis was related to an increased use of guideline recommended treatments. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Danish Heart Foundation